Reproductive maturity in the edible Chilean crab Cancer edwardsii: Methodological and management considerations - Pardo, Luis Miguel (2009)
Size-at-maturity, often used by fisheries managers to specify reference points, was estimated for Cancer edwardsii, the most intensely exploited brachyuran crab in Chile, using morphometric data and observation of the gonadal cycle. Sampling was conducted in Chiloé Island, the principal landing region. Several morphometric measurements of secondary sexual characters were recorded for both sexes. Their size-dependence was investigated in search of ontogenetic allometric changes. Six stages of maturity were established for females, and four for males, on the basis of macroscopic and histological observation of the reproductive system, allowing distinction between adults and juveniles. Females and males, on average, attained full development of secondary sexual characters at 106 and 118mm carapace width (CW) respectively. The CW at which 50% of females and males have gonads of adult appearance was around 101mm. Current minimum legal size is 120mm CW, seemingly high enough for conservation purposes. This management control, however, is unlikely to provide effective protection due to the high proportion of crab of sub-legal size in the landings. Traps with escape vents could be introduced in this fishery in order to ensure its sustainability.